In Vitro Angiotensin-Converting Enzyme (ACE) Inhibition Test on Extract Dayak Onion Herb (Eleutherine americana (Aubl.) Merr. ex K. Heyne) (Sciences of Pharmacy, 2023)
One of the world's silent killer diseases is hypertension. Hypertension occurs when angiotensin I is converted to angiotensin II, causing vasoconstriction and decreasing sodium and water excretion. The mechanism of angiotensin I conversion to angiotensin II appears in the presence of the Angiotensin-Converting Enzyme (ACE). Dayak onion is widely used as an antihypertensive in traditional medicine. This study aims to identify secondary metabolites, determine total flavonoid content, determine extract quality parameters, and ACE inhibitory activity of the Dayak onion herb. Dayak onion herb was extracted with 70% ethanol by kinetic maceration, followed by phytochemical screening, extract quality assessment, and ACE inhibitory test. The results show that the Dayak onion extract has a good properties with total ash content of 4.49%, water-soluble ash content of 4.00%, acid-insoluble ash content of 0.41%, drying shrinkage of 9.70%, water content of 5.72%, solvent residue of 0.67%, Pb heavy metal content of 0.2908 mg/kg, Cd heavy metal content of 0.0880 mg/kg, total plate number ≤103 colonies/g, and yeast mold numbers ≤103 colonies/g. Dayak onions herbs extract contains flavonoid, alkaloid, saponin, tannin, triterpenoid, quinone, steroid and essential oil compounds. The total flavonoid content was 2.24% and the IC50 in ACE inhibitory test was 98.5 ± 0.77 ppm, making it two times more potent than Veronica biloba and Schoenoplectus triqueter. The result of this study indicates that the Dayak onion herb can be used as an alternative for antihypertensive treatment.